Study of training management in archery - Sonia Ariani S; Endarman Saputra; Anggel Hardi Yanto (Sriwijaya Journal of Sport, 2025)
Research Problems: Archery requires precision, concentration, and physical and mental stability. Effective training management is essential to support athlete performance. However, suboptimal implementation is still common, highlighting the need for studies to evaluate and improve training effectiveness in this sport. Research Objectives: This study examines the management of archery training at the Rajawali Archery Club in Jambi City. Methods: A qualitative research method with a case study approach was employed, with data collected through interviews, observations, and document analysis. The data sources comprised the club’s management, coaches, and athletes. Results: The findings reveal that the training management at Rajawali Archery Club encompasses four essential components: planning, organising, directing, and evaluation. The planning process is systematically arranged, involving the formulation of training objectives, target setting, and the implementation of structured training programs. In terms of organisation, the club continues to encounter challenges, particularly concerning inadequate facilities and infrastructure that have yet to meet proper safety standards. Coaching activities are delivered through technical instruction and motivational support for athletes, while evaluations are conducted monthly to monitor athletes’ development and to assess the effectiveness of the training program. Conclusion: The training management at the Rajawali Archery Club is generally well-implemented; however, further improvements in facilities and financial support are necessary to optimise athlete performance and to support the achievement of higher competitive outcomes.